Fa‘âliyatu wasâili at ta‘alî as sam‘iyah al bashariyah ‘alâ dawâfi‘i at ta‘allumi li thâlibâti al fashli at tsânî li mâdati al fiqhi bi ma‘ahadi dârissalâm guntûr li albanât alharam atsâlits - Miftahul Ulum; Rifa Mardhiyyah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Technological innovation has an important role in the learning process. People believe that audio-visual media will be able to motivate the students interested to attend classes with more enthusiastics. Learning situations with initially learning effort will be turned into learning with fun and enjoyable. Because of this advantage, the researcher purpose of this research to review an effectiveness of audio visual teaching media to motivate students class 2 KMI in Fiqh. This study was designed by non-experimental research. The population of this study were 291 students. This study uses a sample which consisting of 158 students counted by random sampling method which taken 5% for trial error. The instrument that been used are questionnaires to determine variable x and y. The data was analysed by product moment. Data analysis for validity test and reliability test was carried out using SPSS 17 for windows. To test the hypotheses that have been formulated by coefficient. Result for score at effectiveness of audio visual teaching media has a range between 37 to 43 average score of 41,3. And score at motivation aspect for Fiqh of of class 2 KMI has a range between 37 to 43 average score of 38. And effectiveness of audio visual teaching media used to motivate students class 2 KMI in Fiqh pointed out r count < r table (0,101< 0,156). Which means of analysis show that effectiveness of audio visual teaching media used to motivate students class 2 KMI in Fiqh learning is low effectiveness.